Project gad-savvy : a health communications campaign educating tertiary students in Singapore about gadget dependency - Giam, Zhen Wei. (2012)
This paper presents the ‘Gad-Savvy’ project, a social health campaign by four undergraduates from the Wee Kim Wee School of Communication and Information. This communication campaign aims to raise awareness on the issue of gadget dependency among Singaporean Youths, aged 17-25 years old. The literature review explores the rising trend of gadget (or portable electronic device) ownership and usage in the light of technological advancements. The report outlines the communication plans and key strategies used. The effectiveness of the campaign is assessed by process and outcome evaluation, and future recommendations are provided.